Tanggap Genotipe Kacang Tanah Terhadap Penyakit Bercak Daun Cercospora dan Karat Daun Puccinia - Alfi Inayati; Eriyanto Yusnawan (Jurnal Fitopatologi Indonesia, 2016)
Leaf spot and rust are two important diseases on groundnut. Both diseases are frequently found at the same time that influence the growth and reduce the yield of groundnut. This study was conducted to evaluate thirteen groundnut genotypes resistance to leaf spot and rust disease.  The experiment was conducted using a split plot design and three replications, with inoculated and uninoculated treatment as main plot, and  groundnut genotypes as the sub plot.  Disease assessment was conducted by counting number of pustules per leaf, the number of spots per leaf, rust disease intensity, the intensity of leaf spot disease, and leaf area index. Yield components including stover weight, number of pods per plant, number of empty pods, number of chipo pods, and weight of pods per plant were recorded for both inoculated and uninoculated plants. The result showed that leaf spot disease developed earlier than rust disease. Only one genotype was susceptible to rust and the other 12 genotypes were very susceptible, whereas all genotypes tested were very susceptible to leaf spot. The intensity of rust and leaf spot diseases was negatively correlated with yield (r = - 0.1 – (0.4)). Rust and leaf spot diseases reduced the yield components including stover weight (73.2%), number of pods (68%), and weight of pods (72.5%). The number of empty pods and chipo pods were increase to 81% and 56.4% respectively.